Picture-based task definition and parameterization support system - Machado, V. (2018)
Applications for task definition and automation are valuable tools to automated software engineering area. This paper describes a solution to support a parameterized task definition using screen capture images. The approach allows the capture of a sequence of actions defined by the user. Through the captured sequence of actions, the approach assists in the implementation of task automation processes. Based on picture-driven computing the proposed tool aims to reduce the challenges that users face while trying to define tasks. This approach provides also a foundation for the creation of picture-driven based tests for interactive systems, enabling to test any interactive system but also allowing for the definition, parameterization and execution of tests that might involve the use of several independent interactive systems.